Evaluation of Overall Survival Predictions In Inoperable Pancreas Ductal Adenocarcinoma - Hasan Önner; Mustafa Erol; İlknur Küçükosmanoğlu (Genel Tıp Dergisi)
Objective: In this study, we aimed to determine the independent predictive parameters of overall survival (OS) ofpatients with inoperable pancreatic ductal adenocarcinoma (PDAC) and to investigate whether these parameterscan be used as potential biomarkers to shape precision medicine practices for PDAC patients.Material and Methods: The clinical and pathological data of patients who were diagnosed with inoperablepancreatic ductal adenocarcinoma between January 2016 and December 2019 and who underwent18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) in our departmentwere retrospectively analyzed. Tumor diameter, maximum standardized uptake value (SUVmax), metabolictumor volume (MTV), and total lesion glycolysis (TLG) were calculated from FDG PET/CT images. Univariate andmultivariate Cox regression analyzes were performed to investigate the variable affecting overall survival. Overallsurvival data were analyzed using the Kaplan–Meier method, using the log-rank test.Results: A total of 48 patients, 31 male and 17 female, with a mean age of 65.85 ± 1.64 were included in the study.In univariate Cox regression analyzes were performed to examine the factor affecting OS. Clinicopathologicalfactors (tumor localization, tumor diameter, stage) and FDG PET/CT parameters (SUVmax, MTV and TLG) with ap-value of < 0.2 were compared to multivariate Cox regression analysis. TLG was found to be the only independentpredictor of OS. In the Kaplan-Meier analysis, the median OS duration of the patients with a median value of TLGbelow 298.34 was 13.87 months, while the median OS duration was found to be 4.97 months in patients with a TLGvalue above this value.Conclusion: In our study, TLG value, which is an FDG PET/CT parameter that reflects both the metabolic activity andthe volume of the tumor, was found to be the only independent predictor of the OS of inoperable PDAC patients.TLG can be used as a potential biomarker for survival in patients with inoperable PDAC and may assist precisionmedicine applications.